Adoption and usage of collaboration information technologies in Australia and New Zealand - Pervan, Graham; Bajwa, D.; Lewis, L. (Idea Group, 2003)
IT can potentially play a significant role in task collaboration if it can enhance the quality of communication and coordination between group members asynchronously or synchronously. This paper empirically assessed the pattern of deployment of IY in supporting task-oriented collaboration in organisat6ions in Australia and New Zealand. Data collected from one hundred and forty-seven organisations is analyzed to gain insights into adoption and use patterns of seven popular IT clusters that have the capability to support collaboration between workgroup members. Our analyses show that e-mail and proprietary groupware are the most widely adopted and used IT while data conferencing tools and electronic meeting systems have the lowest level of both adoption and use.